THE MANY-FACET RASCH MODEL IN THE ANALYSIS OF INSTRUMENTS MEASURING TEACHERS' ATTITUDES TOWARDS EARTHQUAKE DISASTER PREPAREDNESS IN INDONESIA - Arifuddin, Hikmayanti; Arismunandar, Arismunandar; Arifuddin, Adhar; Nur, A Fahira; Arifuddin, Hidayanti; Rahman, Abd (Universitas Tadulako, 2024)
Materials and Methods: This study employed a survey research design with an exploratory quantitative approach using Many-Facet Rasch Model (MFRN) analysis. The data used for the analysis of the assessment instrument measuring teachers' attitudes towards earthquake disaster preparedness in schools were field data obtained from a survey conducted by three raters assessing 33 elementary school teachers in Palu City. The instrument consisted of 20 items, resulting in a total of 1980 collected data points. Results: The item reliability value was 0.94, indicating that the instrument's quality falls within the